Enzymatic functionalization of bacterial nanocellulose: current approaches and future prospects - Monika Kaczmarek; Aneta Monika Białkowska (Journal of Nanobiotechnology)
Abstract Faced with the challenges of modern industry and medicine associated with the dynamic development of civilization, there is a constantly growing demand for the production of novel functional materials that are clearly oriented towards fulfilling specific applications. Herein, we provide an overview of the current status and recent findings related to the enzymatic functionalization of bacterial nanocellulose. Commonly, biocellulose modification involves the utilization of simple and cost-effective chemical and/or physical approaches. However, these methods may have an adverse effect on both the biological properties of the biomaterial and the natural environment. An alternative to these procedures is the highly specific enzymatic modification of bacterial nanocellulose, which perfectly fits into the assumptions of green technologies, making the process eco-friendly and not limiting any outlooks for further usage of the obtained biocomposites. The employment of enzymes for the targeted alteration of this material’s properties is based on either a direct method, such as controlled hydrolysis and nanofication [i.e., synthesis of different morphological forms of bacterial cellulose (e.g., rod-shaped nanocrystals)] using cellulases, and/or attachment of reactive functional groups into the polymer structure via oxidation (e.g., utilizing a laccase/TEMPO catalytic system or lytic polysaccharide monooxygenases) and esterification catalyzed by lipases; or an indirect procedure involving the application of bacterial nanocellulose as a matrix for enzyme immobilization (e.g., laccase, glucose oxidase, horseradish peroxidase, lysozyme, bromelain, lipase, papain), thus creating a specific catalytic system. Overall, enzymatic functionalization of bacterial nanocellulose is a sustainable and promising strategy to create biocomposites with tailored properties for a wide range of industrial and medical applications. Graphical Abstract